Epidemiological Characteristics of COVID-19 Outbreak in Yangzhou, China, 2021 - Zhang, Yu-Dong; Chen, Ding; Hu, Lei; Shen, Liang; Wu, Ren-Yuan; Cao, Fu-Ming; Xu, Jian-Qiang; Wang, Liang (Frontiers in Microbiology, 2022)
Objective: Epidemiological characteristics of the COVID-19 outbreak in Yangzhou city caused by the highly contagious Delta variant strain of SARS-CoV-2 virus were investigated in this retrospective descriptive study to provide prevention and control guidelines for outbreaks in future. Methods: All the epidemiological data used in this study were manually collected from the official website of Yangzhou Municipal Health Committee from July 28 to August 26, 2021 and then were analyzed systematically and statistically in this study. Results: A total of 570 COVID-19 cases were reported during the short-term outbreak in Yangzhou City. Ages of infected individuals ranged from 1 to 90 years with the average age at 49.47 ± 22.69 years. As for gender distributions, the ratio of male to female patients was 1:1.36 (242:328). Geographic analysis showed that 377 patients (66.1%) were in Hanjiang District while 188 patients (33.0%) were in Guangling district. Clinical diagnosis showed that 175 people (30.7%) had mild symptoms, 385 people were in moderate conditions (67.5%), while 10 people were in severe situations (1.8%). Significant age differences were found among the three groups (P-value < 0.001). However, no significant difference was identified in terms of gender ratio (P-value > 0.05). Based on the transmission chain formed by 6 generations of infected persons with clear transmission relationship, the age showed a gradually decreasing trend, while the median time of diagnosis in two adjacent generations was 3 days. In addition, the estimated basic reproduction number R0 of the Delta variant was 3.3651 by the classical Susceptible, Infectious, and/or Recovered (SIR) model. Conclusions: Delta variant of SARS-CoV-2 was highly infectious and has obvious clustering characteristics during the Yangzhou outbreak in China.